Comparing the clinical-effectiveness and cost-effectiveness of an internet-delivered Acceptance and Commitment Therapy (ACT) intervention with a waiting list control among adults with chronic pain: study protocol for a randomised controlled trial. Issue 7 (2nd July 2014) - Hayes, Sara; Hogan, Michael; Dowd, Haulie; Doherty, Edel; O'Higgins, Siobhan; Nic Gabhainn, Saoirse; MacNeela, Padraig; Murphy, Andrew W; Kropmans, Thomas; O'Neill, Ciaran; Newell, John; McGuire, Brian E
Abstract : Introduction: Internet-delivered psychological interventions among people with chronic pain have the potential to overcome environmental and economic barriers to the provision of evidence-based psychological treatment in the Irish health service context. While the use of internet-delivered cognitive–behavioural therapy programmes has been consistently shown to have small-to-moderate effects in the management of chronic pain, there is a paucity in the research regarding the effectiveness of an internet-delivered Acceptance and Commitment Therapy (ACT) programme among people with chronic pain. The current study will compare the clinical-effectiveness and cost-effectiveness of an online ACT intervention with a waitlist control condition in terms of the management of pain-related functional interference among people with chronic pain. Methods and analysis: Participants with non-malignant pain that persists for at least 3 months will be randomised to one of two study conditions. The experimental group will undergo an eight-session internet-delivered ACT programme over an 8-week period. The control group will be a waiting list group and will be offered the ACT intervention after the 3-month follow-up period. Participants will be assessed preintervention, postintervention and at a 3-month follow-up. The primary outcome will be pain-related functional interference. Secondary outcomes will include: pain intensity, depression, global impression of change, acceptance of chronic pain and quality of life. A qualitative evaluation of the perspectives of the participants regarding the ACT intervention will be completed after the trial. Ethics and dissemination: The study will be performed in agreement with the Declaration of Helsinki and is approved by the National University of Ireland Galway Research Ethics Committee (12/05/05). The results of the trial will be published according to the CONSORT statement and will be presented at conferences and reported in peer-reviewed journals. Trial registration number: ISRCTN18166896.